The Executor of Integrated Marketing Communications Strategy: Marcom Manager$1 (Bs Working Models - Shin, Kwang-Yong.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book mainly addresses the following aspects: First, it systematically introduces the domestic and foreign research results, pointing out the key elements of the basic theory of IMC, according to a company$1 (Bs present situation and the practice of IMC strategy. Second, according to the different characteristics of each organization, it provides various IMC organization structures, such as linear structure Model l, a virtual network and centralized type that focuses on individual interest, external types of the IMC organizational structures Model, etc., and suggestions for further study are also presented.s
Introduction -- Organization -- Implementation -- Marcom Manager$1 (Bs Work: Communication Category -- The Working Model of Marcom Manager.s
Keywords: Economics; Marketing; Economics/Management Science; Marketing; Business/Management Science, general